2022
DOI: 10.11591/ijai.v11.i1.pp327-335
|View full text |Cite
|
Sign up to set email alerts
|

Automatic face recording system based on quick response code using multicam

Abstract: This research mainly talks about the use of quick response (QR) code reader in automating of recording the users' face. The applied QR code reader system is a dynamic type, which can be modified as required, such as adding a database, functioning to store or retrieve information in the QR code image. Since the QR code image is randomly based on its information, a QR code generator is required to display the image and store the information. While the face recorder uses a dataset available in the OpenCV library.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Another research [15] is covered that 10 am to 3:59 pm significantly reduces the chance of fatal injuries. Some researchers have used AI-based models for the early detection of intuition [16], [17]. Some studies have shown that heavier cars increase the chance of pedestrian fatalities [18].…”
Section: Related Workmentioning
confidence: 99%
“…Another research [15] is covered that 10 am to 3:59 pm significantly reduces the chance of fatal injuries. Some researchers have used AI-based models for the early detection of intuition [16], [17]. Some studies have shown that heavier cars increase the chance of pedestrian fatalities [18].…”
Section: Related Workmentioning
confidence: 99%
“…Where Faster R-CNN which is a method of object detection that is able to detect an object captured by the camera [21][22] [23]. The workings of the prototype start with the process of detecting whether the object is wearing a mask or not, then if it is wearing a mask, whether it is using a standard mask or not, then the data is sent to the cloud to be sent to the IoT device [24]. So, the door is only open for those who wear masks and use standard masks.…”
Section: Fig 2 Research Flow Mapmentioning
confidence: 99%
“…Where Faster R-CNN which is a method of object detection that is able to detect an object captured by the camera [21][22] [23]. prototype work begins with the detection process on mask detection or not using and whether the mask is used is standard or not so as to support prototype data stored in the cloud network [24]. After the prototype was developed in this paper, the application that was carried out was to provide a detection signal to IoT devices in carrying out automatic door opening for standard mask and mask users.…”
Section: Introductionmentioning
confidence: 99%
“…Before outputting music, the mp3 file required for voice output was placed in the raw folder. If the conditions for color recognition were satisfied, a voice file was output [24]- [28].…”
Section: Voice Outputmentioning
confidence: 99%